Bedaquiline Correlation to QT Interval Prolongation in DR-TB Patients - Vandu Primadana; Indra Yovi; Dyah Siswanti Estiningsih (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: The regimen of drug-resistant tuberculosis (DR-TB) is Bedaquiline. One of the adverse events is QT interval prolongation, which can increase the risk of Torsade de Pointes (TdP) and lead to death. DR-TB patient screening before starting the treatment and monitoring QT interval during the treatment should be performed. This study aimed to determine Bedaquiline correlation to QT interval prolongation in DR-TB patients. Methods: This was a retrospective study using an observational design by viewing medical records of DR-TB patients who underwent treatment from January 2019 to March 2022. Results: This study involved 46 DR-TB patients with an average age of 41.4 years old, and 58.7% were males with a regimen of Bedaquiline. The comparison of Baseline QT intervals before and after one month of therapy showed QT interval prolongation (457.1 ± 18.2 ms and 443.8 ± 10.2 ms; p < 0.001). The comparison of QT intervals before the therapy and six months after the therapy showed prolongation QT intervals (443.8 ± 10.2 ms and 458.4 ± 23.7 ms; p < 0.001). QT intervals after one month of therapy compared to six months after the therapy showed insignificant slight prolongation (457.1 ± 18.2 ms and 458.4 ± 23.7 ms; p = 0.587). Conclusion: QT interval prolongation occurred in DR-TB patients who received treatment using Bedaquiline regimen. It was seen significantly between baseline QT interval and after receiving the therapy for one month and six months.